Insuring Nature's Survival : The Role of Insurance in Meeting the Financial Need to Preserve Biodiversity - World Bank (Washington, DC: World Bank, 2022)
Biodiversity loss will be an increasingly important source of risk and opportunity for the insurance sector. The significant degradation of ecosystems has the potential to materially impact global finance, economies, and societies alike. Understanding the physical and transition risks associated with biodiversity loss and working to mitigate the damage to biodiversity will be a key aspect of meeting the targets set by the Paris Agreement. Insurance companies will be impacted by biodiversity risks in several ways: as underwriters, as investors, and as corporate citizens. Insurers will be impacted both by changes in climate and biodiversity and by transition risks affecting the risks they insure or the investments they make. Insurance can promote investment in biodiversity in three ways: (i) asset protection, (ii) liability reduction, and (iii) facilitation of capital inflow from the financial markets. Ideally, efforts to protect biodiversity will include a combination of instruments, not only insurance. Insurers, as investors, can contribute directly to the preservation of biodiversity by channeling capital towards biodiversity-positive investments, but the opportunities to do so are still limited. The G20 Sustainable Finance Roadmap (G20 SFWG, 2021) highlighted the need to integrate nature and biodiversity in future work on sustainable finance. The financial materiality of underestimating or inaccurately pricing biodiversity-related risks could pose a threat to the solvency of the insurance industry and lead to an increase in exclusions of uninsurable risks. Risk management can be enhanced by combining the results of both catastrophe and climate risk models, but more needs to be done to incorporate biodiversity risk. Combining ecological action with financial protection can make good economic and financial sense and help overcome the pricing issues associated with risks such as wildfire.